Ketimpangan Ketimpangan Sosial dalam Akses dan Praktik Pendidikan Digital di Indonesia - Muhamad Naufal Aqil; Nur Khasanah (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
The transformation of digital technology has opened up enormous opportunities in the world of education in Indonesia. However, not all groups in society can enjoy equal access and benefits of digital education. This study aims to analyze social inequality in digital education in Indonesia through a qualitative approach based on literature studies with illustrative narrative data from mixed communities (rural, urban, lower-middle class and upper-middle class). The results of the study indicate that there are three main dimensions of inequality: (1) access to devices and internet connections, (2) digital literacy and the ability to utilize technology, (3) different outcomes of digital education use between social groups. This inequality indicates that digital education has not fully created equality, and even has the potential to strengthen social reproduction as proposed by Bourdieu. The implications of this study indicate the need for educational policies and practices that emphasize the equal distribution of digital infrastructure, increasing digital literacy, and adapting curricula that are sensitive to socio-economic condition.